Surface Karst Landforms of the Notranjska region (south-western Slovenia) - Gawor, Łukasz; Jonczy, Iwona (Geotourism/Geoturystyka, 2015)
The distribution and characteristics of surface karst landforms in the Notranjska region, exemplifi ed in the Cerknisica and Rak river catchment, is presented. The geomorphology of the examined area, with respect to on the micro-, meso- and macroforms division, is described. The course and dynamics of morphogenetic and geological processes are analyzed. A geotourist route linking the described landforms of surface karst is proposed.